Jelly ice crystal and preparation method thereof
By using polymer resin, organic anhydride, modified pearlescent powder and tert-butyl hydroquinone in jelly ice crystals, the problems of poor aesthetic effect and insufficient mechanical properties of jelly ice crystals in the prior art are solved, and the problem of poor aesthetic effect and insufficient mechanical properties of jelly ice crystals in the prior art are achieved. Beautiful, excellent mechanical properties and simple preparation effect.
Patent Information
- Application Number
- CN202411294358.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
The existing polystyrene/hydrogenated polyisoprene copolymers are used in the application of jelly ice crystals. They have poor aesthetic effects, insufficient mechanical properties and complex processing processes, making it difficult to meet the requirements of many aspects.
Using polymer resin, organic anhydride, modified pearlescent powder and tert-butyl hydroquinone, jelly ice crystals are prepared through specific mixing and reaction steps to improve their mechanical properties and aesthetic effects, and simplify the processing process.
It has achieved the aesthetic effect improvement and optimization of mechanical properties of jelly ice crystals, including improving tensile strength and elongation at break, and simplified the preparation process, meeting the requirements of aesthetics, excellent mechanical properties and simple preparation.
Smart Images

Figure CN119192742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a jelly ice crystal and a preparation method thereof. Background Art
[0002] Polystyrene / hydrogenated polyisoprene copolymers have a wide range of uses, including making disposable containers, foam lunch boxes, cosmetic packaging, etc., and can also be used as film formers, viscosity regulators, light stabilizers, etc. The physical properties of polystyrene / hydrogenated polyisoprene copolymers include hard and brittle texture, colorless and transparent, and can be mixed with a variety of dyes to produce different colors. These properties make them suitable for making a variety of packaging materials and cosmetic packaging.
[0003] At present, the application of polystyrene / hydrogenated polyisoprene copolymer in jelly ice crystals is the latest application field of polystyrene / hydrogenated polyisoprene copolymers. Jelly ice crystals have put forward many requirements for materials, such as: 1. Having an aesthetic effect similar to ice crystals, 2. Having good mechanical properties, 3. Simple preparation and low price, without the need for special processing equipment and complex processes, such as double-roll mills or high-temperature vulcanization processes, etc. The current common jelly ice crystals have different problems and cannot fully meet the requirements, such as not being aesthetically pleasing, low elongation at break, and complex processing.
[0004] In summary, it is urgent to design a jelly ice crystal to solve the problems existing in the prior art. Summary of the invention
[0005] Based on this, the present invention provides a jelly ice crystal, which meets the requirements of aesthetics, excellent mechanical properties and simple preparation method, solves the defects of the prior art and has good application prospects.
[0006] One object of the present invention is to provide a jelly ice crystal, wherein the jelly ice crystal comprises the following components in mass fractions:
[0007] Polymer resin 10-20%
[0008] Organic anhydride 3-8%
[0009] Modified pearl powder 0.5-3%
[0010] Tert-butylhydroquinone 0.5-2%
[0011] Solvent residue;
[0012] The modified pearlescent powder is obtained by reacting acrylic anhydride grafted gelatin and silane coupling agent grafted pearlescent powder.
[0013] Furthermore, the mass ratio of the acrylic anhydride grafted gelatin to the silane coupling agent grafted pearlescent powder is 1:(2-3).
[0014] Furthermore, the polymer resin is a polystyrene / hydrogenated polyisoprene copolymer.
[0015] Furthermore, the solvent is selected from one or more of liquid paraffin, white oil, caprylic / capric triglyceride, isopropyl palmitate, and sucrose polysoybean oleate.
[0016] Furthermore, the organic acid anhydride is selected from one or more of acetic anhydride, succinic anhydride, maleic anhydride and phthalic anhydride.
[0017] Furthermore, the silane coupling agent is an acrylate-based silane coupling agent.
[0018] Furthermore, the pearlescent powder is selected from one or more of titanium dioxide, mica powder, tin oxide and talc.
[0019] The present invention also provides a method for preparing the jelly ice crystals, comprising the following steps:
[0020] S1, mixing a silane coupling agent and pearlescent powder, and heating the mixture to obtain silane coupling agent-grafted pearlescent powder;
[0021] S2, mixing gelatin and acrylic anhydride, and heating the mixture to obtain acrylic anhydride grafted gelatin;
[0022] S3, mixing and reacting the silane coupling agent grafted pearl powder, acrylic anhydride grafted gelatin, and an initiator to obtain modified pearl powder;
[0023] S4, mixing the polymer resin, the solvent and the organic acid anhydride and heating them for reaction, adding the modified pearlescent powder and tert-butylhydroquinone and stirring, and obtaining jelly ice crystals.
[0024] Furthermore, in step S1, the temperature of the heating reaction is 50-80°C.
[0025] Furthermore, in step S1, the mass ratio of the silane coupling agent to the pearlescent powder is 1:(20-40).
[0026] Furthermore, in step S2, the temperature of the heating reaction is 20-50°C.
[0027] Furthermore, in step S2, the mass ratio of gelatin to acrylic anhydride is 10:(9-13).
[0028] Furthermore, in step S2, the solvent of the reaction is a phosphate buffer solution.
[0029] Furthermore, in step S3, the reaction temperature is 40-65°C.
[0030] Furthermore, in step S3, the mass ratio of the silane coupling agent grafted pearl powder, the acrylic anhydride grafted gelatin, and the initiator is (2-3):1:(0.02-0.05).
[0031] Furthermore, in step S3, the initiator is benzoyl peroxide.
[0032] Furthermore, in step S4, the mass ratio of the modified pearlescent powder to tert-butylhydroquinone is (1-1.5):1.
[0033] Furthermore, in step S4, the temperature of the heating reaction is 90-110°C.
[0034] The present invention has the following beneficial effects:
[0035] 1. Gelatin has a large number of polar groups, which can play a role in thickening and viscosity enhancement. However, directly adding gelatin to ice crystal products may lead to reduced mechanical properties, mechanical strength and stability of the material. The present invention first uses acrylic anhydride to modify gelatin, introduces unsaturated double bonds, and then mixes and reacts with pearlescent powder grafted with an acrylate silane coupling agent, thereby introducing active groups such as amino and carboxyl groups on the surface of the pearlescent powder. While exerting the function of gelatin, the compatibility between the modified pearlescent powder and the polystyrene / hydrogenated polyisoprene copolymer resin is enhanced, thereby improving the stability of the product; and the present invention uses organic acid anhydride to modify the polymer resin, which can be further cross-linked with the modified pearlescent powder through chemical bonds and intermolecular forces; the present invention also uses tert-butylhydroquinone as a stabilizer, which not only has good compatibility with other components, but also can form hydrogen bonds with the modified pearlescent powder and the polymer resin to form a more stable structure, thereby improving the stability of the jelly ice crystals and mechanical properties such as tensile strength and elongation at break.
[0036] 2. Pearlescent powder has certain optical properties and can present different colors of luster through refraction, reflection, etc. After adding jelly ice crystals, it can make the jelly ice crystals have a more beautiful appearance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The appearance of the jelly ice crystals prepared in the embodiment is shown;
[0038] in,
[0039] Figure 1 (a) is the appearance of the jelly ice crystals prepared in Example 1;
[0040] Figure 1 (b) is the appearance of the jelly ice crystals prepared in Example 2. DETAILED DESCRIPTION
[0041] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0042] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0043] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers expressing, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that vary depending on the desired properties to be obtained by the present invention.
[0044] Unless otherwise stated, the raw materials, reactions and post-treatment methods in the examples and comparative examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0045] KH570, acrylate-based silane coupling agent, purchased from Nanjing Chuangshi Chemical Additives Co., Ltd.;
[0046] TiO2, pearl powder, particle size 10-30nm;
[0047] Gelatin, food grade, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0048] The polymer resin was polystyrene / hydrogenated polyisoprene copolymer purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., DW3432;
[0049] Phosphate buffer solution, pH=7.4, concentration 0.01 M, purchased from Thermo Fisher Scientific Inc., USA.
[0050] The components and corresponding mass fractions in the jelly ice crystals of Examples 1-3 of the present invention are shown in Table 1.
[0051] Table 1 Components and mass fractions of Examples 1-3
[0052]
[0053] The method for preparing the jelly ice crystals of Examples 1-3 comprises the following steps:
[0054] S1. Using 90wt% ethanol-water mixture as solvent, mix TiO2 and KH570 in a mass ratio of 5:1, heat to 60°C and stir to react for 1h. After stirring, filter and collect the solid, wash with ethanol and dry to obtain silane coupling agent grafted pearl powder;
[0055] S2, add 5g gelatin to 70ml phosphate buffer solution, heat to 50°C, stir for 0.5h, add 5g acrylic anhydride dropwise at a rate of 0.1ml / min, stir for 3h, add 350ml phosphate buffer solution to stop the reaction, transfer to a dialysis bag (model MWCO, molecular weight 12000-14000) for dialysis, freeze-dry for 3 days to obtain acrylic anhydride grafted gelatin;
[0056] S3, using water as solvent, mixing silane coupling agent grafted pearl powder, acrylic anhydride grafted gelatin, and BPO in a mass ratio of 2:1:0.03, heating at 65°C for reaction for 1 hour, filtering, washing, and drying to obtain modified pearl powder;
[0057] S4. Heat the polymer resin to 90°C according to the above mass fraction, then add isopropyl palmitate and stir evenly, add maleic anhydride, stir for 0.5h, add modified pearl powder and tert-butylhydroquinone, stir for 0.5h, pour into a mold, cool and solidify naturally for 6h to obtain jelly ice crystals.
[0058] Figure 1 The appearance of the jelly ice crystals prepared in the embodiment is shown;
[0059] in,
[0060] Figure 1 (a) is the appearance of the jelly ice crystals prepared in Example 1;
[0061] Figure 1 (b) is the appearance of the jelly ice crystals prepared in Example 2.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that step S1 is deleted, and in step S3, the silane coupling agent grafted pearl powder is replaced with unmodified TiO2, and other materials and preparation methods are the same as those in Example 1.
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 1 is that step S2 is deleted, and in step S3, the acrylic anhydride grafted gelatin is replaced with unmodified gelatin. Other materials and preparation methods are the same as those in Example 1.
[0066] Comparative Example 3
[0067] The difference between this comparative example and Example 1 is that maleic anhydride is not added in step S4.
[0068] Test Example 1
[0069] The jelly ice crystals of Examples 1-3 and Comparative Examples 1-3 were tested for appearance and mechanical properties.
[0070] Test method:
[0071] The appearance of the jelly ice crystals was directly observed with the naked eye, and the tensile strength and elongation at break were tested according to GB / T 528-2009 standard.
[0072] The test results are shown in Table 2.
[0073] Table 2 Appearance and mechanical properties test results
[0074] sample Appearance Tensile strength(Mpa) Elongation at break (%) Example 1 Silver transparent solid 43.6 166 Example 2 Silver transparent solid 44.2 170 Example 3 Silver transparent solid 49.8 183 Comparative Example 1 Silver transparent solid 32.6 143 Comparative Example 2 Silver transparent solid 34.3 157 Comparative Example 3 Silver transparent solid 29.9 125
[0075] It can be seen from Table 2 that the jelly crystals of Examples 1-3 and Comparative Examples 1-3 are all silver transparent solids; the tensile strength of Examples 1-3 is greater than 40 MPa, and the elongation at break is greater than 150%, which is significantly higher than that of Comparative Examples 1-3, proving that the present invention can effectively improve the mechanical properties of jelly crystals.
[0076] Test Example 2
[0077] The jelly ice crystals of Examples 1-3 and Comparative Examples 1-3 were subjected to a stability test.
[0078] Test method:
[0079] The products were placed in water, sodium fatty alcohol polyoxyethylene ether sulfate, cocamidopropyl betaine and other solvents, and immersed at different temperatures (5°C, 25°C, 48°C, 60°C) for one month, and the appearance changes of the products and the system were observed.
[0080] The test results at 5°C, 25°C, 48°C and 60°C are shown in Tables 3, 4, 5 and 6 respectively.
[0081] Table 3 Test results at 5℃
[0082]
[0083]
[0084] Table 4 Test results at 25℃
[0085] sample water Fatty alcohol polyoxyethylene ether sodium sulfate Cocamidopropyl Betaine Example 1 No change in product, no change in system No change in product, no change in system No change in product, no change in system Example 2 No change in product, no change in system No change in product, no change in system No change in product, no change in system Example 3 No change in product, no change in system No change in product, no change in system No change in product, no change in system Comparative Example 1 No change in product, no change in system No change in product, no change in system No change in product, no change in system Comparative Example 2 No change in product, no change in system No change in product, no change in system No change in product, no change in system Comparative Example 3 No change in product, no change in system No change in product, no change in system No change in product, no change in system
[0086] Table 5 Test results at 48℃
[0087] sample water Fatty alcohol polyoxyethylene ether sodium sulfate Cocamidopropyl Betaine Example 1 No change in product, no change in system No change in product, no change in system No change in product, no change in system Example 2 No change in product, no change in system No change in product, no change in system No change in product, no change in system Example 3 No change in product, no change in system No change in product, no change in system No change in product, no change in system Comparative Example 1 Product deformation, system failure Product deformation, system failure Product deformation, system failure Comparative Example 2 Product deformation, system failure Product deformation, system failure Product deformation, system failure Comparative Example 3 Product deformation, system failure Product deformation, system failure Product deformation, system failure
[0088] Table 6 Test results at 60℃
[0089] sample water Fatty alcohol polyoxyethylene ether sodium sulfate Cocamidopropyl Betaine Example 1 No change in product, no change in system The product is deformed and the system is not hazy The product is deformed and the system is not hazy Example 2 No change in product, no change in system The product is deformed and the system is not hazy The product is deformed and the system is not hazy Example 3 No change in product, no change in system The product is deformed and the system is not hazy The product is deformed and the system is not hazy Comparative Example 1 Product deformation, system failure Product deformation, system failure Product deformation, system failure Comparative Example 2 Product deformation, system failure Product deformation, system failure Product deformation, system failure Comparative Example 3 Product deformation, system failure Product deformation, system failure Product deformation, system failure
[0090] As can be seen from Tables 3-6, for Example 1-3, at 5°C, 25°C, and 48°C, in solvents such as water, sodium polyoxyethylene fatty alcohol ether sulfate, and cocamidopropyl betaine, the product does not change, and the system does not become hazy. At 60°C, when water is used as the solvent, the product does not change, and the system does not become hazy. When sodium polyoxyethylene fatty alcohol ether sulfate and cocamidopropyl betaine are used as solvents, the product is slightly deformed, and the system does not become hazy, indicating that Example 1-3 has good stability at low temperatures and is still relatively stable at slightly higher temperatures, that is, the embodiment has good stability. For Comparative Examples 1-3, at 5°C and 25°C, the product does not change, and the system does not become hazy. When the temperature is raised to 48°C and 60°C, the products of Comparative Examples 1-3 are deformed and the system becomes hazy, indicating that Comparative Examples 1-3 are relatively stable at low temperatures. As the temperature rises, the product is deformed, the system becomes hazy, and the stability is poor.
[0091] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0092] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A jelly ice crystal, characterized in that: The jelly ice crystals include the following components by mass fraction: Polymer resin 10-20% Organic anhydride 3-8% Modified pearl powder 0.5-3% Tert-butylhydroquinone 0.5-2% Solvent residue; The modified pearlescent powder is obtained by reacting acrylic anhydride grafted gelatin and silane coupling agent grafted pearlescent powder.
2. The jelly ice crystal according to claim 1, characterized in that: The mass ratio of the acrylic anhydride grafted gelatin to the silane coupling agent grafted pearl powder is 1:(2-3).
3. The jelly ice crystal according to claim 1, characterized in that: The polymer resin is a polystyrene / hydrogenated polyisoprene copolymer.
4. The jelly ice crystal according to claim 1, characterized in that: The organic acid anhydride is selected from one or more of acetic anhydride, succinic anhydride, maleic anhydride and phthalic anhydride.
5. The jelly ice crystal according to claim 1, characterized in that: The silane coupling agent is an acrylate-based silane coupling agent.
6. The jelly ice crystal according to claim 1, characterized in that: The pearlescent powder is selected from one or more of titanium dioxide, mica powder, tin oxide and talc.
7. The method for preparing jelly ice crystals according to any one of claims 1 to 6, characterized in that: The method for preparing jelly ice crystals comprises the following steps: S1, mixing a silane coupling agent and pearlescent powder, and heating the mixture to obtain silane coupling agent-grafted pearlescent powder; S2, mixing gelatin and acrylic anhydride, and heating the mixture to obtain acrylic anhydride grafted gelatin; S3, mixing and reacting the silane coupling agent grafted pearl powder, acrylic anhydride grafted gelatin, and an initiator to obtain modified pearl powder; S4, mixing the polymer resin, the solvent and the organic acid anhydride and heating them for reaction, adding the modified pearlescent powder and tert-butylhydroquinone and stirring, and obtaining jelly ice crystals.
8. The method for preparing jelly ice crystals according to claim 7, characterized in that: In step S1, the temperature of the heating reaction is 50-80°C.
9. The method for preparing jelly ice crystals according to claim 7, characterized in that: In step S2, the temperature of the heating reaction is 20-50°C.
10. The method for preparing jelly ice crystals according to claim 7, characterized in that: In step S3, the reaction temperature is 40-65°C; in step S4, the heating reaction temperature is 90-110°C.
